Diagnóstico de la carga mental en los docentes de la ULEAM extensión Bahía de Caráquez - Briones Cantos, Camila Yamileth (2024)
The purpose of this research was to determine the mental workload of the faculty at Universidad Laica Eloy Alfaro, Manabí, Bahía de Caráquez extension, to improve job performance. Methodologies and techniques were employed that allowed for addressing the subject of study, which was divided into three stages. In the first stage, relevant theoretical foundations for the diagnosis were identified through a literature review. In the second stage, an interview with the dean was conducted, along with surveys of the faculty. In the third stage, an improvement plan was proposed, with strategies and solutions to mitigate the identified issues. The study revealed significant problems related to cognitive demands and task complexity; 50% of the surveyed teachers indicated that the complexity of the information they use for their work is very high. Additionally, they reported memorizing a large amount of information and material to carry out their tasks. It is concluded that the institution must implement preventive measures to address these psychosocial risks, which negatively impact both family and work life. This research provides a valuable contribution to the university community. Furthermore, an improvement plan was developed and presented to all faculty members, explaining the level of cognitive risks and the recommended preventive measures. These actions are essential to promoting a healthy and sustainable academic environment. The effective implementation of these measures will significantly contribute to the overall well-being of the educational community.